(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Two new deep-sea hatchetfish species, †Argyropelecus iranicus n. sp. and †Argyropelecus zagrosensis n. sp., are described in detail herein based on fossil material from the Eocene (Bartonian) deposits of the Pabdeh Formation, Zagros Basin, Iran. A detailed investigation of the skeletal morphology of these new species was made possible through elemental distribution maps obtained using micro-XRF imaging technique of the fossil material. These new species are the oldest known representatives of the genus Argyropelecus. A phylogenetic analysis that includes all the extant species of the genus Argyropelecus suggests that †Argyropelecus iranicus n. sp. and †Argyropelecus zagrosensis n. sp. pertain to the ‘A. lychnus species complex’ and the ‘A. affinis species complex’, respectively. The morphospace analysis confirmed the presence of two distinct morphotypes within the genus Argyropelecus. Potential correlations between morphospace occupation and the ecological setting and lifestyle of this bizarre group of deep-sea fishes are also discussed. The presence of two species of the genus Argyropelecus in the Eocene Pabdeh Formation extends the temporal and biogeographical range of these deep-sea fishes, providing additional information for our understanding of the evolutionary and biogeographical history of the deep-sea hatchetfishes.